2021
DOI: 10.1186/s12913-021-07299-y
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of nutritional risk in the acute care setting: progress towards a practice and evidence informed systems level approach

Abstract: Background To improve nutritional assessment and care pathways in the acute care setting, it is important to understand the indicators that may predict nutritional risk. Informed by a review of systematic reviews, this project engaged stakeholders to prioritise and reach consensus on a list of evidence based and clinically contextualised indicators for identifying malnutrition risk in the acute care setting. Methods A modified Delphi approach was e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[17,18] Dysphagia poses significant challenges to the rehabilitation and quality of life of patients. [19,20] Physiologically, patients may face a lack of sufficient nutrition and water, increasing the risk of inhalation pneumonia, thereby affecting the rehabilitation process and quality of life; psychologically, difficulty swallowing may lead to patients experiencing fear of food intake, anxiety, depression, and even social barriers. [21][22][23] In the past few decades, nursing strategies for stroke patients have been continuously optimized, but the management of swallowing difficulties still faces a series of challenges.…”
Section: Discussionmentioning
confidence: 99%
“…[17,18] Dysphagia poses significant challenges to the rehabilitation and quality of life of patients. [19,20] Physiologically, patients may face a lack of sufficient nutrition and water, increasing the risk of inhalation pneumonia, thereby affecting the rehabilitation process and quality of life; psychologically, difficulty swallowing may lead to patients experiencing fear of food intake, anxiety, depression, and even social barriers. [21][22][23] In the past few decades, nursing strategies for stroke patients have been continuously optimized, but the management of swallowing difficulties still faces a series of challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors identified an error in all the author names. The given name and family name were erroneously transposed.…”
mentioning
confidence: 99%